Muse, ninfe e sirene. Un incontro in libreria - Autori Vari (Il sogno della farfalla, 2006)
The debate, held during a meeting of the editorial committee of “Il sogno della farfalla”, on 23 October 2005, sparked off by the questions raised by two musicians, the pianist Enrico Pieranunzi and the singer Ada Montellanico, in their respective articles published in this issue of the magazine. To the question regarding the reason why there are so few women composers, Fagioli offers an answer which goes beyond the obvious historical and social conditioning, taking into consideration the differences that exists between men and women without introducing judgements of superiority/ inferiority. A woman can represent for a man the image of the first year of his life without conscience, and therefore the necessary internal reality for artistic creation, as the myths tell us through the muses and nymphs. Representing a similar image seems more difficult for a man to accomplish, who reaches a symbolization of the written language through the loss of images and the realization of indifference, if not a lack of affects, which contrasts with the reality of women.